Variation of Residual Chlorine Concentration in Some Regions of Al_Rassafa - A. Rammadhan , Ahmad; B. Nada , Kamal; A. Jassam , Ban (Iraqi Journal of Science, 2022)
This study was done to examine the concentration of residual chlorine from different regions at AL Risafa side. The samples were collected from Baghdad AL- Jadida, Shareaa Phlistain, AL- Shaab and AL- Habibea, Al-Karrada, Al-Jadria, Al-Adamia at April-August/2013 .The Electrical Conductivity (Ec) and total dissolve solid (TDS), hang about its normal rate according to (WHO) but the Turbidity go beyond it’s limit to reach (11NTU) where the highest peak was recorded in Baghdad AL Jadida. The results show that chlorine concentration were decreased in the August compared with April because of high Temperature, and long in sun shine duration. It is found that there is inverse proportionality between residual chlorine and temperature. Same trend was found between residual chlorine and turbidity. The Conductivity and total dissolved solids of drinking water was within the permitted level according the Iraqi Standers (IQS, 2009).